Animations and depictions as a tool to improve pre-service elementary teachers' noticing of students' mathematical thinking - Sumeyra Dogan Coskun (Journal of Pedagogical Research, 2024)
The purpose of the study is to examine pre-service elementary teachers' noticing of students' mathematical thinking of division through animations and depictions. For this purpose, the data was collected from pre-service teachers' written explanations of important moments identified when watching a video clip, as well as pre-service teachers' animations and depictions of classroom scenarios. Findings indicated that what the pre-service teachers noticed in the video clip was more general, as they attended to the whole class environment, students' behaviours and learning in total, and teacher pedagogy. The pre-service teachers, however, were more focused on particular students' mathematical thinking in their animations and depictions. Furthermore, between animations and depictions, the pre-service elementary teachers included the most details about students and teachers in the latter one. Therefore, this study concludes that while both preparing animations and depictions have a positive effect on the pre-service elementary teachers' noticing levels, preparing depictions better facilitates their attention to students' thinking about mathematics.